Test studies of layout of container with apples in body of car (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article reveals the features of methodological substantiation of analytical studies of the layout of the container with apples in the body of the car. The theoretical study established factors of the external and internal environment that affect the parameters of the duration of transportation and damage to agricultural cargo. A mathematical model is proposed that describes the carriage of goods from several suppliers to several consumers, taking into account weather and road conditions. General and private research methods were applied to practically verify the conclusions of the theoretical research. The general methodology of research is based on national and international standards and technical conditions on acceptance rules, methods of determination of quality, packaging, transportation, which apply to fruit and vegetable products in general and apples in particular.
Keywords: car; body; operation; apple; container